1991
DOI: 10.1099/00222615-35-1-23
|View full text |Cite
|
Sign up to set email alerts
|

Isoation and characterisation of an extracellular alkaline protease of Aspergillus fumigatus

Abstract: Summary. Aspergillus fumigatus secreted an inducible alkaline protease (AlPase) when cultivated in the presence of collagen (200pg/ml) as sole nitrogen and carbon source. Proteolytic activity was maximum at pH 9-0 with azocollagen as substrate. The enzyme, which was the major protein found in the supernate of a liquid culture, was purified by ammonium sulphate precipitation and gel filtration. The Mr was determined to be 33 Kda by gel filtration and sodium dodecyl sulphate-polyacrylamide gel electrophoresis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
106
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 18 publications
11
106
0
2
Order By: Relevance
“…In previous studies, an extracellular alkaline protease from A. fumigatus with a molecular mass of 33 kDa and a pI of 8n2 has been demonstrated by several laboratories [22][23][24][25][26][27]. Furthermore, this enzyme was able to degrade collagen, elastin and fibrinogen, and to induce epithelial cells to detach from the basement membrane [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, an extracellular alkaline protease from A. fumigatus with a molecular mass of 33 kDa and a pI of 8n2 has been demonstrated by several laboratories [22][23][24][25][26][27]. Furthermore, this enzyme was able to degrade collagen, elastin and fibrinogen, and to induce epithelial cells to detach from the basement membrane [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this enzyme was able to degrade collagen, elastin and fibrinogen, and to induce epithelial cells to detach from the basement membrane [26][27][28][29]. It was suggested that such an extracellular protease may be involved in the pathogenesis of aspergillosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that changes in growth media can have large effects on the profile of proteins that are secreted during fungal growth [29,30]. For example, growth of Aspergillus species in the presence of collagen has been shown to induce expression of an alkaline protease [31], a fibrinogenolytic enzyme in the presence of peptone [32], and an esterase in the presence of sugar-beet pulp [33]. There are likely many as yet undiscovered applications for enzymes produced by Aspergillus and other microbial species awaiting discovery.…”
Section: Introductionmentioning
confidence: 99%
“…In composts, this fungus plays an important role in the decomposition of organic material and in recycling environmental carbon and nitrogen (Beffa et al, 1998). Like many other ascomycetes from the soil, A. fumigatus grows well in media containing protein as the sole nitrogen and carbon source and shows secreted proteolytic activity (Reichard et al, 1990;Monod et al, 1991;Sriranganadane et al, 2010). At neutral pH, the fungus secretes two endoproteases, an alkaline protease (Alp) of the subtilisin family (Reichard et al, 1990;Monod et al, 1991) and a metalloprotease (Mep) of the fungalisin family (Monod et al, 1993a, b;Jaton-Ogay et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Like many other ascomycetes from the soil, A. fumigatus grows well in media containing protein as the sole nitrogen and carbon source and shows secreted proteolytic activity (Reichard et al, 1990;Monod et al, 1991;Sriranganadane et al, 2010). At neutral pH, the fungus secretes two endoproteases, an alkaline protease (Alp) of the subtilisin family (Reichard et al, 1990;Monod et al, 1991) and a metalloprotease (Mep) of the fungalisin family (Monod et al, 1993a, b;Jaton-Ogay et al, 1994). In addition, A. fumigatus secretes leucine aminopeptidases (Laps), which are non-specific monoaminopeptidases, dipeptidyl-peptidases (DppIV and DppV) and a prolylpeptidase (AfuS28) as exopeptidases (Beauvais et al, 1997a, b;Monod et al, 2005;Sriranganadane et al, 2010).…”
Section: Introductionmentioning
confidence: 99%